Molecular evolution and structural variations in nuclear encoded chloroplast localized heat shock protein 26 (sHSP26) from genetically diverse wheat species. (December 2019) - Suneja, Yadhu; Gupta, Anil Kumar; Chhuneja, Parveen; Bains, Navtej Singh
Graphical abstract: Highlights: Identification and in silico characterization of choloroplast specific HSP26 allelic variants in wild relatives of wheat. A novel HSP26 gene discovered in DD-genome assembly of diploid progenitor wheat, the orthologue of which -is not present in hexaploid wheat genome. First report -on the isolation of a novel chloroplast specific sHSP26 protein from Ae. tauschii accession pau14376 (GenBank:MN119514). A 9-bp indel in TmHSP26-1(GA) translated into a deletion of SPM amino acid segment in chloroplast specific conserved consensus region III. High degree of divergence in nucleotide sequence between cultivated and wild species appeared in the form of higher ω values (Ka/Ks >1). Abstract: Heat shock proteins are an important class of molecular chaperones known to impart tolerance under high temperature stress. sHSP26, a member of small heat shock protein subfamily is specifically involved in protecting plant's photosynthetic machinery. The present study aimed at identifying and characterizing sequence and structural variations in sHSP26 from genetically diverse progenitor and non-progenitor species of wheat. In silico analysis identified three paralogous copies of TaHSP26 to reside on short arm of chromosome 4A while one homeologue each was localized on long arm of chromosome 4B and 4D of cultivated bread wheat. Wild DD-genome donor Aegilops tauschii carried an additional sHSP26 gene (AET4Gv20569400) which was absent in the cultivated DD genome of bread wheat. In vitro amplification of this novel gene in wild accessions of Ae. tauschii and synthetic hexaploid wheat but not in cultivated bread wheat validated this finding. Further, significant length polymorphism could be identified in exon1 from diverse sHSP26 sequences. Multiple sequence alignment of procured sequences revealed numerous sSNPs and nsSNPs. D3A, P125 L, Q242 K were designated as homeolog specific- while A49 G as non-progenitor specific amino acid replacements. A 9-bp indel in TmHSP26-1(GA) translated into a deletion of SPM amino acid segment in chloroplast specific conserved consensus region III. High degree of divergence in nucleotide sequence between cultivated and wild species appeared in the form of higher ω values (Ka/Ks >1) indicating positive selection during the course of evolution. Phylogenetic analysis elucidated ancestral relationships between wheat sHSP26 proteins and orthologous proteins across plant kingdom. Overall, data mining approach may be employed as an effective pre-breeding strategy to identify and mobilize novel stress responsive genes and distinct allelic variants from wider germplasm collections of wheat to enhance climate resilience of present day elite wheat cultivars.